The pathogenetic aspects of measles virus infection: memorandum from a WHO meeting. - Billeter, M; Bellini, W; Vanbinnendijk, R; Borrow, P; Brown, F; Cutts, F; Fennelly, G; Gellin, B; Griffin, D; Katz, S; Kolakofsky, D; Kreth, H; et al. (1994)
Over the last three years considerable progress has been made in various areas related to measles virus and infection. A meeting to discuss the currently available data on the molecular biology of measles virus, measles immunology, immunopathology, as well as animal models for measles infection, and to identify studies that need to be carried out towards developing new vaccines was organized jointly by WHO and the U.S. National Institutes of Health and held in Montreux, Switzerland, on 20-21 April 1993. This Memorandum summarizes the discussions and recommendations made by the participants.